The role of c-reactive protein as an inflammatory marker in normal postpartum: A case study at RSUD, dr. Soekardjo Tasikmalaya - Noviana, Dilla; Meri, Meri; Yulianti, Dewi Kania (Institute of Computer Science (IOCS), 2024)
The normal delivery process is often followed by pain caused by a ruptured pervaginal wound, which can be the primary focus for assessing the degree of inflammation in the body. The presence of inflammation remains a major concern. One of the most commonly used indicators of inflammation is C-reactive protein (CRP) in response to inflammation, infections, or tissue injury. aimed at measuring CRP levels in normal postpartum patients who have been allowed to return to the hospital, Dr. Soekardjo Tasikmalaya. The samples were taken through purposive sampling and consisted of 30 patients from RSUD Dr. Soekardjo City, Tasikmalaya. The inclusion criteria in this study included patients who did not have a history of diseases such as diabetes, tuberculosis (TB), or lupus. While the exclusion criteria included the refusal of subjects to be respondents and samples who underwent hemolysis and have met the ethical test of the research with the number 043-01/E.01/KEPK-BTH/V/2024. The results of the C-reactive protein examination showed that 26 samples (86,7%) showed positive results and 4 samples (13,3%) showed negative results. So it can be concluded that normal postpartum mothers still have inflammation, especially on the first day.